IMPLEMENTASI BARCODE DETECTION DENGAN METODE OPERASI MORFOLOGI UNTUK SISTEM INVENTARISASI - Muhammad Najib (Universitas Islam Balitar Blitar, 2022)
Technological developments that are so fast require us to be able to display information quickly and precisely on the inventory system, there is so much data, how can we present the data needed quickly, one way is by using a barcode so that the system can communicate directly in need of a barcode scanner. to be able to detect and read the barcode in order to be able to connect directly to the server, therefore a barcode detection system was made using morphological methods to improve barcode detection.